Unequal access to land: Consequences for the food security of smallholder farmers in sub Saharan Africa - Wijk, Mark T. van; Hammond, James; Frelat, Romain; Fraval, Simon (Elsevier, 2019)
Smallholder farms are crucial to feed the planet but are also food insecure. This chapter uses quantitative data on smallholder systems across sub Saharan Africa to analyse the consequences of unequal land access. Variation in farm size is large and looks different in different regions. Commonly used thresholds to define smallholders are therefore over-simplifications and the relationship between farm size and food security is complicated. Farm sizes are changing rapidly and we need to better understand the consequences for food security to more efficiently target interventions to improve the well-being of the vulnerable rural populations.